Family support in carrying out online learning during the COVID-19 pandemic - Desmon Wirawati; Fischa Awalin (International Journal of Health Science and Technology, 2023)
The Covid-19 pandemic brought changes in learning methods, where the government issued regulations requiring education stakeholders to implement distance learning or online learning to reduce the incidence of Covid-19. The policy issued is not an easy thing for students, teachers, and families to live. Therefore, family support is one factor determining the achievement of online learning. This study aims to determine family support in the implementation of online learning for students during the Covid 19 pandemic. The research method used is exploratory descriptive using a cross-sectional approach. The research was conducted in June 2021 at the Faculty of Nursing, Cendekia Abditama University. The instrument used was a list of questions or questionnaires with a number of research samples was 144 respondents. The results showed that family support in online learning in the information aspect was in the good category (54.9%), in the emotional aspect in the good category (58.3%), family support in the appreciation aspect (52.8%), and family support in the instrumental aspect in the good category (60.4%). Family is a good supporter of an online learning process.